Translation, cross-cultural adaptation, and validation of the heart disease fact questionnaire among the Brazilian population - Shimoya-Bittencourt,Walkiria (2022)
SUMMARY OBJECTIVE: This study aimed to translate, cross-culturally adapt, and validate the Heart Disease Fact Questionnaire into Brazilian Portuguese. METHODS: The Brazilian version of the Heart Disease Fact Questionnaire was developed through the processes of translation, back-translation, review committee, and pre-test. Test-retest reliability was measured using the intraclass correlation coefficient and the kappa coefficient. Internal consistency was measured using Cronbach's alpha. For construct validity, the total Heart Disease Fact Questionnaire score was correlated with the Diabetes Knowledge Scale and the Diabetes Attitudes Questionnaire. Ceiling and floor effects were also evaluated in this study. RESULTS: For construct validity and floor and ceiling effect measurements, a total of 100 participants were selected. Reliability was measured using a sub-sample of 30 participants from the total sample. We identified adequate values of reliability (kappa between 0.22 and 1.00 and ICC=0.75) and internal consistency (Cronbach's alpha=0.79). We observed adequate correlations of the Heart Disease Fact Questionnaire score with Diabetes Knowledge Scale (r=0.348) and Diabetes Attitudes Questionnaire (r=0.136). No ceiling or floor effects found. CONCLUSION: Brazilian Portuguese version of the Heart Disease Fact Questionnaire has adequate psychometric properties according to the best scientific recommendations.